2020
DOI: 10.1111/eth.13012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of alarm calls of the oriental tit (Parus minor) toward different predators and reactions they induce in nestlings

Abstract: Anti‐predatory strategies of birds are diverse and may include predator‐specific alarm calls. For example, oriental tit (Parus minor) parents can distinguish snakes from other predators and produce snake‐specific referential vocalizations ("jar" call) when a snake poses a threat to their nest. The “jar” call has a very specific function to induce fledging of nestlings close to fledging age. This reaction ensures nestlings' survival in natural encounters with snakes that are capable of entering nest cavities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…Predator composition may also be an important factor driving the evolution of avian vocal repertoire. In Asia and southern Europe, there are several species of snakes that depredate on birds (Ha et al, 2020; Sorace et al, 2000), whereas in northern Europe, most snake species are unable to climb trees and therefore do not represent a threat to birds. Consequently, snake‐specific alarm calls may not have evolved in northern Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Predator composition may also be an important factor driving the evolution of avian vocal repertoire. In Asia and southern Europe, there are several species of snakes that depredate on birds (Ha et al, 2020; Sorace et al, 2000), whereas in northern Europe, most snake species are unable to climb trees and therefore do not represent a threat to birds. Consequently, snake‐specific alarm calls may not have evolved in northern Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Research has thus far demonstrated that some wild birds' and primates' vocalizations can be characterized as having a lexical or word-like character, in the sense that they denote concepts (e.g., predators in alarm calls or foods in food calls) similarly to how words in human languages denote (i.e., mean, map to) certain concepts (Gill and Bierema 2013;Macedonia and Evans 1993;Townsend and Manser 2013;Zuberbühler 2009). This has been reported for different taxa, including, for example, chickens (Gallus; Evans et al 1993;Karakashian et al 1988), trumpeters (Psophia; Seddon et al 2002), tits (Paridae; Ha et al 2020;Haftorn 2000;Suzuki 2011Suzuki , 2012Suzuki , 2014Suzuki , 2015Suzuki , 2016aSuzuki , b, 2018Suzuki , 2019Suzuki , 2020Suzuki , 2021, titi monkeys (Callicebinae; Cäsar et al 2012;Schlenker et al 2017), capuchins (Cebinae;Digweed et al 2005), macaques (Macaca; Brumm et al 2004), Chlorocebi (including vervets and green monkeys; Cheney and Seyfarth 1990;Fischer 2020;Lyn and Christopher 2020;Seyfarth et al 1980a, b;Snowdon 2020;Struhsaker 1967), guenons (Cercopithecus;Arnold et al , 2010Arnold and Zuberbühler 2006b;Zuberbühler et al 1999), and chimpanzees (Pan; Clay and Zuberbühler 2009;Crockford and Boesch 2003;Slocombe and Zuberbühler 2005;…”
Section: Semantic Compositionality In Wild Animal Communicationmentioning
confidence: 94%
“…We describe each of them below. Several metrics are frequently used when examining mob calls, including the number of individuals calling, (Arnold, 2000;Coomes, McIvor, & Thornton, 2019;Królikowska, Szymkowiak, Laidlaw, & Kuczyński, 2016), call type (Carlson, Healy, & Templeton, 2017b;Suzuki, 2014) call rate, (Bartmess-LeVasseur, Branch, Browning, Owens, & Freeberg, 2010;Coppinger, Kania, Lucas, Sieving, & Freeberg, 2020;Cross & Rogers, 2006), and detailed acoustic measurements (Carlson, Greene, & Templeton, 2020;Courter, Perruci, McGinnis, & Rainieri, 2020;Furrer & Manser, 2009;Ha et al, 2020;Kalb & Randler, 2019;Manser et al, 2014).…”
Section: How Is Mobbing Measured?mentioning
confidence: 99%